2020
DOI: 10.1088/1361-6463/ab77de
|View full text |Cite
|
Sign up to set email alerts
|

Quench-rate and size-dependent behaviour in glassy Ge2Sb2Te5 models simulated with a machine-learned Gaussian approximation potential

Abstract: Phase-change memory materials are promising candidates for beyond-silicon, next-generation non-volatile-memory and neuromorphic-computing devices; the canonical such material is the chalcogenide semiconductor alloy Ge2Sb2Te5. Here, we describe the results of an analysis of glassy molecular-dynamics models of this material, as generated using a newly developed, linear-scaling (O(N)), machine-learned, Gaussian approximation potential. We investigate the behaviour of the glassy models as a function of different q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…285 Subsequently, simulations with simulation-cell sizes up to 24,300 atoms were carried out using the same potential, systematically addressing the role of the simulation-cell size as well as that of the quench rate on the resulting structures. 298 …”
Section: Applications (I): Force Fieldsmentioning
confidence: 99%
“…285 Subsequently, simulations with simulation-cell sizes up to 24,300 atoms were carried out using the same potential, systematically addressing the role of the simulation-cell size as well as that of the quench rate on the resulting structures. 298 …”
Section: Applications (I): Force Fieldsmentioning
confidence: 99%
“…However, a previous analysis on Ge 2 Sb 2 Te 5 shows minor changes in the structural properties of the amorphous phase by doubling the quenching rate from 5 K/ps to 10 K/ps. 43 Reducing the quenching rate to 1 K/ps lead instead to partial crystallization as this material is a very poor glass former. 43 In another work, 44 it was shown that two amorphous models of GeTe generated by quenching from 1000 K to 300 K in either 100 ps or 3 ns featured very similar structural properties provided that in the long quench (3 ns) the quenching rate was faster (≥ 1 K/ps) in the 700-500 K range to prevent crystallization.…”
Section: Computational Detailsmentioning
confidence: 99%
“…43 Reducing the quenching rate to 1 K/ps lead instead to partial crystallization as this material is a very poor glass former. 43 In another work, 44 it was shown that two amorphous models of GeTe generated by quenching from 1000 K to 300 K in either 100 ps or 3 ns featured very similar structural properties provided that in the long quench (3 ns) the quenching rate was faster (≥ 1 K/ps) in the 700-500 K range to prevent crystallization. Several simulations of the supercooled liquid phases of GeTe and Ge 2 Sb 2 Te 5 show that the time scale of few tens of ps used in our production runs is much shorter than the typical incubation time (several hundreds of ps) for the formation of crystalline nuclei in the temperature range 700-500 K where nucleation rate and crystal growth velocities are high.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[ 6 ] It has also been used to simulate very large models of g‐ GST (up to 24 300 atoms), and glassy models of GST quenched from the liquid at rates as slow as 1 K ps −1 . [ 7 ]…”
Section: Introductionmentioning
confidence: 99%